If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2(x + -6) = 7(x + 1) + 2 Reorder the terms: 9x + -2(-6 + x) = 7(x + 1) + 2 9x + (-6 * -2 + x * -2) = 7(x + 1) + 2 9x + (12 + -2x) = 7(x + 1) + 2 Reorder the terms: 12 + 9x + -2x = 7(x + 1) + 2 Combine like terms: 9x + -2x = 7x 12 + 7x = 7(x + 1) + 2 Reorder the terms: 12 + 7x = 7(1 + x) + 2 12 + 7x = (1 * 7 + x * 7) + 2 12 + 7x = (7 + 7x) + 2 Reorder the terms: 12 + 7x = 7 + 2 + 7x Combine like terms: 7 + 2 = 9 12 + 7x = 9 + 7x Add '-7x' to each side of the equation. 12 + 7x + -7x = 9 + 7x + -7x Combine like terms: 7x + -7x = 0 12 + 0 = 9 + 7x + -7x 12 = 9 + 7x + -7x Combine like terms: 7x + -7x = 0 12 = 9 + 0 12 = 9 Solving 12 = 9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(x+9)=19 | | 4x+4=60 | | 11r+5=-2r^2 | | (2x+12)/(3x+12)=8/11 | | y=12.5x+200 | | 1.7(7-x)=1.5(5-x) | | x*2-21=15-3x*2 | | 6x-9-2x=x+2+x | | 3x+2+5=40 | | 18t+54/3=36t-27/3 | | 3/4/0.5 | | 42+5*10+6/2 | | 3145/37 | | 3p-16=p+4 | | 42-4*3+9/3 | | 4(y+2)=36 | | 4500=3000(1+0.08*t) | | 42-5*4+6/2 | | 1/2+0.5 | | 12r+4r+(4-6/4r) | | 6a+5/6a=12-4/3 | | x^4+5x^3-20x-16=0 | | 25x=100+50 | | y-7/3=7y+13 | | X^2+18X=40 | | h=-4.9t^2+19.6t-9.6 | | 3.2*10-.5x=17.7x*10 | | 600x+5000=170 | | 3x-7=5x+3(x-4) | | 2(3-2x)+6=6x | | 5/x+6/5x^2 | | 8x-3x=105 |